A primary study of the Jilin-Heilongjiang high-pressure metamorphic belt: Evidence and tectonic implications - Zhou, Jian-Bo; Han, J.; Wilde, Simon; Guo, X.; Zeng, W.; Cao, J. (Science China Press, 2013)
Jilin-Heilongjiang high-pressure metamorphic belt (Ji-Hei HP Belt), around western and southern margin of the Jiamusi-Khanka block, is the high-pressure metamorphic belt with the accretionary complex due to the subduction of the Jiamusi-Khanka block with the Songliao and North China blocks. The Ji-Hei HP Belt consists of the western accretionary complex belt to the west, and the Changchun-Yanji accretionary complex belt to the south. The western accretionary complex belt consista of Heilongjiang blueschist belt and Zhangguangcai-Xiaoxingan Range complex belt. This belt under greenschist to blueschist facies conditions ware between 180Ma and 210Ma, following collision between the Jiamusi-Khanka and Songliao blocks. In contract, the Changchun-Yanji accretionary complex belt consists of subduction-accretion complex, including Shitoukouman-Yantongshan piemontiteschist, Hulan metamorphic complex, Seluohe metamorphic complex, Qinglongcun metamorphic complex and Kaishantun metamorphic complex. The timing for the greenschist to blueschist facies of the Jilin-Yanji accretionary complex belt ware between 187Ma and 230Ma, with pack age at 220~230Ma. The Ji-Hei HP Belt did not result from subduction between the Siberia and North China cratons, but instead was due to subduction of the Pacific Ocean from the east. The Latest Triassic is thus the time when major north-south subduction in the Central Asian Orogenic Belt (CAOB) had ceased and westward-directed Pacific Ocean plate subduction commenced in NE China.